Modeling and design of a new conductance probe for Gas Void Fraction measurement of two-phase flow through annulus. (December 2021) - Ghendour, Nabil; Azzi, Abdelwahid; Meribout, Mahmoud; Zeghloul, Ammar
Abstract: Gas-liquid two-phase flow in annulus channels is encountered in several industrial applications, and the Gas Void Fraction ( GVF ) measurement of such flow is crucial for either monitoring or controlling processes. However, the challenging constraints surrounding annular channels, such as the relatively small distance between the inner and outer pipelines and the non-intrusive accessibility to the inner pipeline, made the GVF measurement difficult to be handled using existing GVF measurement techniques. This paper suggests a new multi-electrodes conductance probe to accurately measure the GVF within annulus flow. The design was finalized after several iterative tunings, followed by an optimization step where a new objective function was suggested to maximize the measurement sensitivity by searching for the optimal relative placement of the electrodes. This was facilitated using COMSOL Multiphysics software, where extensive numerical simulations were done on two types of conductance probes. This has led us to conclude that the new suggested conductance probe, namely 2.2RE probe, which consists of 2 × 2 ring electrodes, can yield a high measurement sensitivity within the target sensing domain, in terms of electric field homogeneity and concentration, using a reasonable amount of hardware compared to other previous works. Indeed, two-dimensional (2D) and three-dimensional (3D) visualization of the current streamlines showed the ability of the 2.2RE probe to handle more efficiently different two-phase flow configurations in the annulus. Furthermore, the geometry of the 2.2RE probe was optimized after a comprehensive analysis of the probe dimensions' effect on its performance. Series of experiments were conducted on a 2.2RE prototype which was designed according to the optimal dimensions to assess the probe response for bubbly and annular flow patterns. The maximum GVF value which was experimentally considered for bubbly and annular patterns were 0.31 and 0.95, respectively. The 2.2RE probe showed a slight dependency on the flow pattern where it exhibited a linear and quasi-linear relationships of the probe output voltage function of the GVF for bubbly and annular flow patterns, respectively. The comparison of experimental and numerical data revealed that the numerical model matches well the experimental data with a maximal relative error of 7.32 % . A calibration procedure of the 2.2RE probe was initiated and assessed numerically, and an accurate estimation of the GVF could be achieved . Graphical abstract: Image 1 Highlights: Numerical simulations of two prior conductance probes in annulus were performed. New 2 × 2 ring conductance probe adapted for annulus was modeled and optimized. 2.2RE probe exhibits a better sensitivity and can be applied for full GVF range. Prototype was built to analyze 2.2RE performance and validate the numerical model. Calibration curve of 2.2RE was experimentally defined and numerically assessed.